Identification and Functional Studies of MYO1H for Mandibular Prognathism. (December 2018) - Sun, R.; Wang, Y.; Jin, M.; Chen, L.; Cao, Y.; Chen, F.
Mandibular prognathism (MP) is regarded as a craniofacial deformity resulting from the combined effects of environmental and genetic factors, while the genetically predetermined component is considered to play an important role to develop MP. Although linkage and association studies for MP have identified multiple strongly associated regions and genes, the causal genes and variants responsible for the deformity remain largely undetermined. To address this, we performed targeted sequencing of 396 genes selected from previous studies as well as genes and pathways related with craniofacial development as primary candidates in 199 MP cases and 197 controls and carried out a series of statistical and functional analyses. A nonsynonymous common variant of MYO1H rs3825393, C>T, p.Pro1001Leu, was identified to be significantly associated with MP. During zebrafish embryologic development, expression of MYO1H orthologous genes were detected at mandibular jaw. Furthermore, jaw cartilage defects were observed in zebrafish knockdown models. Collectively, these data demonstrate that MYO1H is required for proper jaw growth and contributes to MP pathogenesis, expanding our knowledge of the genetic basis of MP.